INFLUENCE OF PROFESSIONAL DEVELOPMENT ON THE EFFECTIVE CONTENT DELIVERY OF ENTREPRENEURSHIP EDUCATION BY BUSINESS EDUCATORS IN SOUTH-SOUTH (NAU Journal of Technology and Vocational Education, 2025)
This study investigated the influence of professional development on the effective content delivery of entrepreneurship education by business educators in South-South, Nigeria. Two purposes, research questions and two hypotheses guided the study. The study adopted a descriptive survey research design. The population of the study comprised of 55 Business Educators that were randomly selected from the state-owned universities in South- South Nigeria. The data for the study was collected with a self-structured questionnaire titled “Questionnaire on influence of Professional Development on the Effective Content Delivery of Entrepreneurship Education”. The instrument was validated by three experts, two in Business Education, and the other one from Measurement and Evaluation.  The reliability of the instrument was established with Cronbach alpha and a reliability coefficient of 0.81 was established.  The data collected was analyzed with mean and standard deviation while t-test was used to test the hypotheses formulated in the study.  Findings in the study shows that; the trainings gotten by Business Educators enhance their creativity, productive and professionalism.  Collaboration amongst deepens their understanding and enhances collective attainment of the goals of the Business Educators and mentoring of Business Educators enhance their career development, pedagogical skills and enhances their level of professionalism.  Based on the findings, conclusion and recommendations made by the researcher in-service training should be provided for Business Educators that teach Entrepreneurship Education in Nigerian Universities.
Keywords: Professional development; content delivery; entrepreneurship education